The Role of Early Childhood Emotional Regulation in Shaping Social Competence: A Longitudinal Analysis - Zohra; Sonila Ali; Rija Ahmed; Anum Zahid Awan; Saria Rafiq; Nusrat Jabeen, (Dialogue Social Science Review (DSSR), 2025)
Natural development in early childhood relies on emotional regulation together with social competencies and display of behavioral strengths. The ongoing assessments help trace development alterations to uncover methods which create the most beneficial results for interventions. The study outcomes become vulnerable when participants drop out of the research and when contextual factors vary between groups. This research analyzed the effects of testing length on emotional control together with social abilities and behavioral capabilities in children across five years along with participant maintenance numbers in diverse municipalities. Three hundred six-to-seven-year-old children participated in this study coming from four different cultural settings. The assessments took place throughout the year from April 2019 to January 2024 at four points. Standardized evaluations measured emotional regulation together with social skills (SSIS) and the behavioral strengths (SDQ) of the participants. The evaluation examined how many participants stayed throughout the research period. Dating assessments from April 2019 to January 2024 resulted in substantial positive changes for children in their emotional regulation abilities and their social skills development along with their behavioral performance improvement. Social skills demonstrated the biggest improvement throughout Years 3 and 4 and after those two years the gains in emotional regulation and behavioral strengths became more noticeable. The number of participants who stayed in the study differed between cities as the final test only included 125 children. The keeping of students in the study proved different based on their social standing as well as their parents' involvement and school backing system. Follow-up analysis demonstrates that continuous support programs lead to better mental development in children. Thorough adjustments to retention strategies must be developed because participant numbers show significant variations. Future studies need to investigate economic inequalities that prevent children from completing assessments while evaluating their growth past childhood years.